Antibacterial Studies of Nickel(II) Complexes of Heterocyclic Schiff Base - Sleema, B.; Ramesh Babu, M.G. (Asian Journal of Chemistry, 2016)
The antibacterial activities of a series of nickel(II) complexes of heterocyclic Schiff bases have been carried out against different bacteria isolated from soil and prawn.